Investigating the Role of Culture in Legal Practices in Spain - Majedeh Bozorgi (Ars Iuris Salmanticensis, 2023)
Law, as the science that organizes and regulates society, will inevitably change its method and approach with the change in social relations. Developments, especially in the field of public law, with the speed with which the laws adopted in the legislative process cannot be adapted and updated with them, have made other sources of law, such as judicial procedure, have different functions. The following article seeks to examine and analyze the question of whether culture has influenced the formation of judicial procedure in Spanish public law. And in case of a positive answer, in what form? The results of the positive response to the developments in the contemporary world and their impact on the science of law are the judicial procedure in three parts: a) creating and establishing new norms, b) supplementing the existing norms in the legal system, c) protect the rights and freedoms of individuals, which have been recognised as a consequence of the status of judicial proceedings among the sources of public law and its promotion.